IMPLEMENTATION OF QUR'AN MEMORIZATION LEARNING AT THE ADLANIYAH MODERN ISLAMIC BOARDING SCHOOL IN WEST PASAMAN - Anisah; Novialdi; Soibatul Aslamiah Nasution (Amanah Publishing, 2024)
This study aims to analyze the implementation of Tahfidzul Qur'an learning at the Adlaniyah Modern Islamic Boarding School in West Pasaman, with a focus on the methods used, supporting and inhibiting factors, and the results achieved by students in the memorization process. The type of research used is qualitative research with a descriptive approach. Data were obtained through observation, interviews with the head of the foundation, tahfidz teachers, and students, and supported by documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the tahfidz program was carried out systematically through the talaqqi and muraja'ah methods which have proven effective in guiding students. Supporting factors include a conducive Islamic boarding school environment, teacher and parental support, and the availability of adequate facilities and infrastructure. Meanwhile, inhibiting factors include limited time, lack of student motivation, difficulties in tajwid, and the emergence of boredom in memorizing. Overall, the implementation of tahfidz learning at the Adlaniyah Modern Islamic Boarding School in West Pasaman has gone well, but there is still a need for innovation in methods, increased motivation, and the use of more varied learning strategies to improve the quality of students' memorization.